Ecology of Anopheline (Diptera, Culicidae), malaria vectors around the Serra da Mesa Reservoir, State of Goiás, Brazil: 1 - Frequency and climatic factors - Guimarães Anthony Érico; Gentile Carla; Alencar Jeronimo; Lopes Catarina Macedo; Mello Rubens Pinto de (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2004)
The ecology of anopheline species (Diptera, Culicidae) was studied in the vicinity of the Serra da Mesa Reservoir, State of Goiás, Brazil. Climatic factors and frequency of anopheline populations were analyzed. Bimonthly human-bait and Shannon trap captures were conducted for 36 consecutive months (January 1997 through December 1999). A total of 5,205 adult anophelines belonging to five species were collected. Anopheles darlingi was the most frequently collected anopheline (61.4%), followed by An. albitarsis s.l. (35.4%), An. triannulatus. (2.5%), An. oswaldoi (0.4%), and An. evansae (0.2%). The water level and vegetation along the banks of the reservoir were crucial to the frequency of the various anopheline species. Climatic factors had a secondary influence. The reservoir's water-level stability, increased frequency of An. darlingi, and the arrival of gold prospectors were responsible for the increase in malaria cases.